An examination of the Apo-1/Fas promoter Mva I polymorphism in Japanese patients with multiple sclerosis - Niino, Masaaki (BioMed Central, 2002)
BACKGROUND: The Apo-1/Fas (CD95) molecule is an apoptosis-signaling cell surface receptor belonging to the tumor necrosis factor (TNF) receptor family. Both Fas and Fas ligand (FasL) are expressed in activated mature T cells, and prolonged cell activation induces susceptibility to Fas-mediated apoptosis. The Apo-1/Fas gene is located in a chromosomal region that shows linkage in multiple sclerosis (MS) genome screens, and studies indicate that there is aberrant expression of the Apo-1/Fas molecule in MS. METHODS: Mva I polymorphism on the Apo-1/Fas promoter gene was detected by PCR-RFLP from the DNA of 114 Japanese patients with conventional MS and 121 healthy controls. We investigated the association of the Mva I polymorphism in Japanese MS patients using a case-control association study design. RESULTS: We found no evidence that the polymorphism contributes to susceptibility to MS. Furthermore, there was no association between Apo-1/Fas gene polymorphisms and clinical course (relapsing-remitting course or secondary-progressive course). No significant association was observed between Apo-1/Fas gene polymorphisms and the age at disease onset. CONCLUSIONS: Overall, our findings suggest that Apo-1/Fas promoter gene polymorphisms are not conclusively related to susceptibility to MS or the clinical characteristics of Japanese patients with MS.